O ATENDIMENTO DE CRIANÇAS COM NECESSIDADES EDUCACIONAIS ESPECIAIS EM CRECHES E PRÉ-ESCOLAS DA REDE MUNICIPAL NA CIDADE DE SÃO LUÍS-MA - Batista, Roseliny de Morais Martins (2012)
This work consists of a general study aimed to understand how to give care to children with NEE in day care centers and municipal preschools in the city of Sao Luis-MA, to characterize a specific way, as theorists of child development and learning, how does the mental training of children with regard to cognitive, social and psychosexual, whether children audience of special education or not; describe the bibliographic research and from official documents, as may be inclusive careto children, specifically, the target audience of special education, like know what these students are assisted in. Early Childhood Education; know which resources used, the procedures and activities performed in crèches and preschools with these children from the speech of teachers, administrators and parents and from observations made at school; characterize the structure and the school learning spaces where the procedures are developed, and activities offered to all children. Finally, reflect on management provided to children audience of special education in the researched Institutions in the light of theories, research and documents studied also has been important. The theoretical foundation is based on authors who speak of the historical background of early childhood education in Brazil, and the inclusion, in addition to the MEC documents that guide about the operation of day care centers and pre-schools in Brazil. We studied child development and learning, based on some authors of philosophy, psychoanalysis and educational psychology. We studied child development and learning, based on some educators and theorists such as Educational Psychology: Piaget, Vygotsky and Freud. The field of qualitative and quantitative was developed in tenmunicipal schools of São Luís in Maranhão, and the participants were the managers, teachers and parents of children with NEE. Semi-structured interviews were applied to each subject. Besides the interviews, participant observations were made in the school context. The technique of content analysis was used to organize and interpret the data. This study revealed that there is a proposal for inclusion in Childhood Education, but that is not yet effective in the context of municipal schools. The inclusion of children with NEE is a recent proposal that requires social action, education and policies to be made effective. The special students enrolled in school search are attended because teachers and administrators are trying to equal opportunities for learning, since the resources and spaces are not in accordance with the needs of all students. The mothers are satisfied with the schools, despite the difficulties. In relation to students with NEE enrolled in the institutions surveyed there is a predominance of children with disabilities and pervasive developmental disorders.